THE EXISTENTIAL SIGNIFICANCE OF CEREMONIAL ARCHES FOR THE ENVIRONMENTAL IMAGE OF THE KERATON AREA IN CIREBON AND YOGYAKARTA - Kirana Zerlinda (Riset Arsitektur (RISA), 2017)
Abstract - The Special Region of Yogyakarta (DIY) and the town of Cirebon are places that share the same monarchical background. This has made urban space planning and the lay-out develop certain characteristics leading to a uniqueness or urban identity. This planning has taken on a physical shape discernible in the environmental image. It has been shaped by the local cultural activities. Ceremonial arches (gates called gerbang) can be regarded as physical elements to be found in Cirebon and Yogyakarta that have cultural-historical value as icons representing the urban environmental image. However, changes made in environmental planning (leading to chaos by prioritizing private interests) has diminished the existence of the physical element of these gerbang At present DIY still adheres to (or recognizes) its monarchical cultural traditions in terms of the public authorities, but Cirebon’s case is different. The latter no longer employs the system for public governance of its region, and at present the historiographic remnants have ended up as mere internal assets.These two differences will naturally affect urban spatial planning and its physical elements, especially when it comes to the characteristic gerbang. In the area of Keraton Kasultanan Ngayogyakarta there are physical elements unlike a proper ceremonial arch, but in socio-cultural terms the Pojok Benteng has been interpreted as a gerbang marking the border of the kingdom’s region. On the other hand, in the area of Keraton Kasepuhan, socio-cultural values affect the interpretation of other physical elements as falling under the gerbang category. These ceremonial arches have ended up as mere markers of “thereness” in the palatial area of the Keraton, which is caused by many other factors that hamper these gerbang gates so that there is no more indication of their actual existence.Keywords: Existence, Socio-cultural, Ceremonial Arch, Urban Image, Expression